A Rare Clinical Finding of Pseudomyxoma Peritonei in a Case of Abnormal Uterine Bleeding - K V, Swetha; Bharathi, Bharathi; Velayudham, Damodhara; Kala, Kala (Journal of Neonatal Surgery, 2025)
Pseudomyxoma peritonei (PMP) is a rare condition marked by mucinous ascites and widespread peritoneal tumor deposits, most commonly arising from a perforated mucinous tumor of the appendix. This case report presents an atypical manifestation of PMP in a patient who initially presented with abnormal uterine bleeding. The report highlights the clinical presentation, diagnostic workup, and therapeutic approach. The patient exhibited progressive abdominal distension, discomfort, and gastrointestinal symptoms. Diagnostic confirmation was achieved through detailed clinical evaluation, radiological imaging, and histopathological analysis. Surgical management involved cytoreductive surgery followed by hyperthermic intraperitoneal chemotherapy (HIPEC), which significantly enhanced the patient's prognosis. Although PMP is uncommon, early recognition and prompt intervention are critical for improving outcomes. The combined approach of cytoreductive surgery and HIPEC remains the current gold standard in treatment. This case emphasizes the need for heightened clinical suspicion and a coordinated, multidisciplinary strategy to achieve optimal patient care